The Challenges and Opportunities of Entering the Social Media Sphere: A Case Study of Polish Cities - Sędkowski, Michał (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
The social media sphere is growing in Poland as more and more people embrace the new ways of communication. Cities in Poland are also slowly catching up with the social media revolution as all 16 provincial cities are present on Facebook. Profiles are static in nature and have problems with engaging the audience in any kind of meaningful conversation. The purpose of this article is to indicate the key challenges that cities are facing while entering the social sphere. Official profiles of all provincial cities in Poland will be analysed to highlight possible ways of improving their digital image.